Mind the Gap: Why Closing the Doughnut Hole Is Insufficient for Increasing Medicare Beneficiary Access to Oral Chemotherapy - Dusetzina, Stacie B. (J Clin Oncol, 2016)
PURPOSE: Orally administered anticancer medications are among the fastest growing components of cancer care. These medications are expensive, and cost-sharing requirements for patients can be a barrier to their use. For Medicare beneficiaries, the Affordable Care Act will close the Part D coverage gap (doughnut hole), which will reduce cost sharing from 100% in 2010 to 25% in 2020 for drug spending above $2,960 until the beneficiary reaches $4,700 in out-of-pocket spending. How much these changes will reduce out-of-pocket costs is unclear. METHODS: We used the Medicare July 2014 Prescription Drug Plan Formulary, Pharmacy Network, and Pricing Information Files from the Centers for Medicare & Medicaid Services for 1,114 stand-alone and 2,230 Medicare Advantage prescription drug formularies, which represent all formularies in 2014. We identified orally administered anticancer medications and summarized drug costs, cost-sharing designs used by available plans, and the estimated out-of-pocket costs for beneficiaries without low-income subsidies who take a single drug before and after the doughnut hole closes. RESULTS: Little variation existed in formulary design across plans and products. The average price per month for included products was $10,060 (range, $5,123 to $16,093). In 2010, median beneficiary annual out-of-pocket costs for a typical treatment duration ranged from $6,456 (interquartile range, $6,433 to $6,482) for dabrafenib to $12,160 (interquartile range, $12,102 to $12,262) for sunitinib. With the assumption that prices remain stable, after the doughnut hole closes, beneficiaries will spend approximately $2,550 less. CONCLUSION: Out-of-pocket costs for Medicare beneficiaries taking orally administered anticancer medications are high and will remain so after the doughnut hole closes. Efforts are needed to improve affordability of high-cost cancer drugs for beneficiaries who need them.